Green School Module: The practicality test in scientific performance skills training for junior high school students - Hendra Hendra; Muhammad Zaini; Dharmono Dharmono (Master Program of Biology Education, Universitas Lambung Mangkurat, 2022)
This development research aims to describe the green school module on the scientific performance skills of junior high school students. The stages of development include self-evaluation, expert test, individual test, small group test, field test. The research subjects were five students for the response test and three observers for the green school module implementation test for the scientific performance skills of junior high school students. The type of data is descriptive data, using the instrument implementation of the module and student responses are used for the practicality of the content and the practicality of expectations. Technical data analysis was carried out in accordance with the objectives of the research which included the practicality of the module. The results showed that the module that had been developed was stated to be very practical based on the individual test. This module was stated to be very good with an average of 89.10%. The module is declared practical because the results of student responses with an average value of 88.34% with very good criteria, the results of the implementation of the module with an average value of 88.10% with criteria strongly agree. Based on this, the developed module is very practical to use and makes it easier for students to learn.Abstrak Penelitian pengembangan ini bertujuan untuk mendeskripsikan modul sekolah hijau pada keterampilan unjuk kerja ilmiah siswa SMP. Tahapan pengembangan meliputi evaluasi diri, uji ahli, uji individu, uji kelompok kecil, uji lapangan. Subjek penelitian ini adalah lima siswa untuk tes respon dan tiga orang pengamat untuk tes implementasi modul sekolah hijau untuk keterampilan unjuk kerja ilmiah siswa SMP. Jenis datanya adalah data deskriptif, dengan menggunakan instrumen implementasi modul dan respon siswa digunakan untuk kepraktisan isi dan kepraktisan harapan. Teknis analisis data dilakukan sesuai dengan tujuan penelitian yang meliputi kepraktisan modul. Hasil penelitian menunjukkan bahwa modul yang telah dikembangkan dinyatakan sangat praktis berdasarkan tes individu. Modul ini dinyatakan sangat baik dengan rata-rata 89,10%. Modul dinyatakan praktis karena hasil respon siswa dengan nilai rata-rata 88,34% dengan kriteria sangat baik, hasil implementasi modul dengan nilai rata-rata 88,10% dengan kriteria sangat setuju. Berdasarkan hal tersebut, modul yang dikembangkan sangat praktis digunakan dan memudahkan siswa untuk belajar.